INCREASE THE EMPLOYMENT LEVEL OF THE POPULATION IN ENSURING THE STABILITY OF ECONOMIC GROWTH - Fatimabonu Alisher kizi Daniyorova (Labor economics and human capital, 2023)
This article describes the impact of economic growth on the lifestyle of the population. A system of socio-economic factors affecting youth employment has been analyzed. Scenarios for the development of the youth labor market according to socio-economic factors affecting it have been proposed. On the basis of econometric models, medium-term forecast values are developed on the main indicators that represent the standard of living of the population. Also, scientifically based proposals have been developed to increase the employment level of the population in ensuring the stability of economic growth.